An Analysis of Financial Supervision of School Management at SMP Sint Carolus of Bengkulu City - Suyanto Suyanto; Ahmad Soleh; Zahrah Indah Ferina (Penerbit Jurnal Indonesia, 2021)
The purpose of this research is to find out the financial supervision of school management at SMP Sint Carolus Bengkulu City. The sample in this study was 30 people consisting of teachers, administrative staff and committee boards at SMP SINT Carolus Bengkulu City. The data collection method in this study was using the questionnaire method. The analytical method used is multiple linear regression, determination test and hypothesis. The results of the regression equation have a positive direction, namely Y = 0.798 + 0.238X1 + 0.360 X2 + 0.298X3 + 0.355X4+e. Planning has a positive and significant influence on SBM management at Sint Carolus Middle School Bengkulu City with a significant value of 0.029, which is smaller than 0, 05. This illustrates that as planning increases, the management of SBM at Sint Carolus Middle School in Bengkulu City will also increase. This illustrates that as programming increases, SBM management at SMP Sint Carolus Bengkulu City will also increase. Budgeting shows a positive and significant influence on SBM Management at SMP Sint Carolus Bengkulu City with a significant value of 0.006 less than 0.05. This illustrates that as budgeting increases, SBM management at SMP Sint Carolus Bengkulu City will also increase. Evaluation has a positive and significant influence on SBM management at SMP Sint Carolus Bengkulu City with a significant value of 0.017, which is smaller than 0.05. This illustrates that the higher the evaluation, the management of SBM at SMP Sint Carolus Bengkulu City will also increase. Planning, programming, budgeting and evaluation have a significant and joint effect on the Management of SBM at SMP Sint Carolus Bengkulu City with a significant value of 0.000 less than 0.05. This illustrates that if there is attention to planning, programming, budgeting and evaluation, SBM management will increase.